Digital Literacy: How Generation Z's Made a Choice Decision Based on Celebrities’ Opinions in Social Media - Fadlan Agustina Firdaus; Aliva Diva Kamila; Arina Faila Saufa (UPT Perpustakaan UIN Alauddin Makassar, 2023)
Born in an era of technological advancement, Generation Z is closely connected to and familiar with the digital world. Information spreads rapidly in the digital age, originating from various sources, including opinions expressed by celebrities. These opinions can easily gain widespread attention through the use of social media. However, it's important to note that such information is sometimes biased and lacks a factual basis.This can lead to a significant influence on users' decision-making processes, as they may rely on celebrity opinions. In this study, we aim to analyze how Generation Z responds to celebrity opinions when making information-related decisions. We will use the DigCom 2.0 framework, focusing on digital literacy components. We will employ a qualitative descriptive method, providing a clear description of how individuals make information-related decisions based on celebrity opinions, with the subject research being Library Science Student at UIN Sunan Kalijaga. The findings indicate that information disseminated by celebrities is often regarded as opinion rather than fully trusted information. It is essential to verify such information. The level of trust depends on various factors, including the celebrity's image, background, achievements, and expertise in the subject matter. Favoritism by celebrities toward specific groups can introduce bias into the information, making it necessary to avoid unquestioned trust. Whether a celebrity is an idol or an ordinary person is not the primary factor in making information-related decisions. Instead, trust in digital capabilities plays a crucial role in decision-making compared to information provided by celebrities who may not have expertise in a particular field.Our study emphasizes the importance of information and data literacy in digital content, encompassing the search process, filtering, evaluation, and information management. These are fundamental aspects of making informed decisions based on celebrity opinions.